Ativismo judicial: o supremo tribunal federal fazendo escola e como nem sempre devemos seguir o mestre / Judicial Activism : The Federal Supreme Court making school and how we should not always follow the master - Silva, Bruno Miola da (Revista do Programa de Pós-Graduação em Direito, 2015)
The aim of the present work is to demonstrate how judges are being protagonists of antidemocratic judgments, in order to include situations which, in theory, the legal text would not contain, exceeding the normative scope of the text. Thus, it is about a study that projects itself for better control of judicial decisions, so that they are not issued on a discretionary way. Therefore, it was sought to basis in the doctrine to identify the reasons that led the Brazilian judges to act in an activist way. In this sense, it is initially made a possible differentiation between judicial activism and legalization and the benefits or harms of such conducts. It was also sought trough recent judicial decisions to demonstrate by sampling that these decisions considered activists do not respect the semantic limits of a text and its interpretation , decisions of this kind that are increasingly proliferating by the judiciary , which creates legal uncertainty due the instability caused by the lack of legal test when the judge renders his decision. Finally, conclusions were presented in order of which may be the limits of interpretation of a text and how extrapolating these limits may damage democracy.